Digital Image–Based Document Authenticity Analysis Using The Daus Approach Through Texture Feature Extraction And Visual Characteristics - Ritna Wahyuni; Firdaus (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Document authenticity is a critical issue in administrative, academic, and legal environments due to the increasing ease of document manipulation using digital technologies. This research focuses on analyzing document authenticity based on digital image processing by utilizing the DAUS approach through texture feature extraction and visual characteristics. The problem addressed in this study is how to effectively distinguish between authentic and manipulated documents using image-based analysis. The proposed approach involves processing scanned or photographed document images to extract texture features and visual cues, such as surface patterns, ink distribution, and structural inconsistencies, which may indicate alterations. These features are then analyzed to identify differences between original and non-original documents. The results of the analysis demonstrate that the combination of texture features and visual characteristics can provide meaningful information for detecting document authenticity. This study concludes that digital image–based analysis using the DAUS approach offers a promising alternative to manual inspection, enabling a more objective and systematic method for document verification. The findings are expected to contribute to the development of reliable document authentication systems in various practical applications.